LOCAL AUTHORITIES IN THE SYSTEM OF STATE GOVERNMENT OF UKRAINE - Kotkovskyi V.R. (Pressing Problems of Public Administration, 2016)
The structure of government of Ukraine, de nes the role and place of local authorities in public relations management.